Moving between jobs. An analysis of occupation distances and skill needs - Bechichi, Nagui; Grundke, Robert; Jamet, Stéphanie; Squicciarini, Mariagrazia (Paris, 2018)
"This paper aims to inform policies facilitating job-to-job transitions triggered by changes in the task content of occupations and in job demand. It assesses the distances existing between occupations in terms of cognitive skills and of skills as they emerge from the tasks performed on the job, and the training needs that moving between occupations entails. Skill “shortages” and “excesses” calculated on data for 31 countries and aggregated over 127 occupations are used to estimate the training efforts required to meet the skills requirements of the destination job. Distances in cognitive skills are found to be higher among low-skilled or from mid- to high-skilled occupations than among higher-skilled occupations. Conversely, distances in task-related skills are higher within high-skilled than low-skilled occupations. These results call for policies aimed at developing general cognitive skills complemented by task-related skills for workers in low-skilled occupations, and on-the-job training options for workers in high-skilled occupations."